Ethyl pyruvate protects rats from phosgene‐induced pulmonary edema by inhibiting cyclooxygenase2 and inducible nitric oxide synthase expression. Issue 1 (5th August 2011) - Chen, Hong‐li; Bai, Hua; Xi, Miao‐miao; Liu, Riu; Qin, Xu‐jun; Liang, Xin; Zhang, Wei; Zhang, Xiao‐di; Li, Wen‐li; Hai, Chun‐xu
ABSTRACT: Phosgene is a poorly water‐soluble gas penetrating the lower respiratory tract which can induce acute lung injury characterized by a latent phase of fatal pulmonary edema. Pulmonary edema caused by phosgene is believed to be a consequence of oxidative stress and inflammatory responses. Ethyl pyruvate (EP) has been demonstrated to have anti‐inflammatory and anti‐oxidative properties in vivo and in vitro . The potential therapeutic role of EP in phosgene‐induced pulmonary edema has not been addressed so far. In the present study, we aim to investigate the protective effects of EP on phosgene‐induced pulmonary edema and the underlying mechanisms. Rats were administered with EP (40 mg kg −1 ) and RAW264.7 cells were also incubated with it (0, 2, 5 or 10 µm ) immediately after phosgene (400 ppm, 1 min) or air exposure. Wet‐to‐dry lung weight ratio (W:D ratio), nitric oxide (NO) and prostaglandin E2 (PGE2 ) production, cyclooxygenase2 (COX‐2) and inducible nitric oxide synthase (iNOS) expression, and mitogen‐activated protein kinases activities (MAPKs) were measured. Our results showed that EP treatment attenuated phosgene‐induced pulmonary edema and decreased the level of NO and PGE2 dose‐dependently. Furthermore, EP significantly reduced COX‐2 expression, iNOS expression and MAPK activation induced by phosgene. Moreover, specific inhibitors of MAPKs reduced COX‐2 and iNOS expression induced by phosgene. These findings suggested that EP has a protective role against phosgene‐induced pulmonary edema, which is mediated in part by inhibiting MAPK activation and subsequently down‐regulating COX‐2 and iNOS expression as well as decreasing the production of NO and PGE2 . Copyright © 2011 John Wiley & Sons, Ltd. Abstract : Phosgene can induce fatal pulmonary edema. Oxidative stress and inflammatory responses are believed to be involved in this process. In the present study, we aim to investigate the therapeutic effects of ethyl pyruvate (EP) on phosgene‐induced pulmonary edema and the underlying mechanisms. We found that EP had a protective role against phosgene‐induced pulmonary edema, which was mediated in part by inhibiting MAPK activation and subsequently down‐regulating COX‐2 and iNOS expression as well as decreasing the production of NO and PGE2 .